2002
DOI: 10.1002/pd.322
|View full text |Cite
|
Sign up to set email alerts
|

Fetal magnetocardiography: development of the fetal cardiac time intervals

Abstract: FMCG provides sufficient information about all parts of the fetal cardiac conduction system from the 19th gestational week on. It offers the possibility to analyse the shape and the duration of the PQRST-complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…The best detection rates prior to this study were reported by K ä hler et al [14] , who also had a 100 % detection rate for QRS and P waves starting at 19 weeks GA. T wave was lowest in early GAs below 24 weeks and increased up to 100 % with a mean for all ages of 93 % (Table 3). With the fi rst dedicated fetal MEG device, it was also possible to detect QRS in 100 % of the cases; however, P wave and T wave detection increased with GA to 95.1 % and 87.3 % , respectively, but detection rates prior to 20 weeks of GA remained challenging [18] .…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The best detection rates prior to this study were reported by K ä hler et al [14] , who also had a 100 % detection rate for QRS and P waves starting at 19 weeks GA. T wave was lowest in early GAs below 24 weeks and increased up to 100 % with a mean for all ages of 93 % (Table 3). With the fi rst dedicated fetal MEG device, it was also possible to detect QRS in 100 % of the cases; however, P wave and T wave detection increased with GA to 95.1 % and 87.3 % , respectively, but detection rates prior to 20 weeks of GA remained challenging [18] .…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, the data match the fi ndings from two existing MCG multicenter studies with the largest MCG data pool. More variation was found compared to the CTIs reported in the literature [13,14,21] . Longer durations were seen in the study by Comani et al [5] .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, some controversy exists on this point. Some reports showed that PR intervals are independent of gestational age [9,19,20]. …”
Section: Discussionmentioning
confidence: 99%
“…At this stage, longer QT and corrected QT intervals were reported in fetal magnetocardiography and noninvasive fetal electrocardiography (14,15). More importantly, the rate of sudden death is higher in the uterus than at most other times in the human life cycle.…”
mentioning
confidence: 91%